A preface to Keats - Watts, Cedric Thomas (London ; New York : Longman, 1985)
Discusses the life and work of John Keats in the social and political context of the world and time in which he lived.
Includes indexes.
Bibliography: p. 181-184.
Keywords: Keats, John, -- 1795-1821.; Keats, John, -- 1795-1821.; Poets, English -- 19th century -- Biography; Poets, English